Effectiveness of Village Fund Management on Community Welfare in Muara Muntai Ulu - Kuryadi, K.; Daulay, Pardamean; Rulandari, Novianita (Manunggal Halim Jaya, 2026)
This study aims to analyze the effectiveness of Village Fund management in improving community welfare in Muara Muntai Ulu Village, Muara Muntai District, Kutai Kartanegara Regency. Although Village Funds have been directed to finance various priority sectors such as basic infrastructure development, education, health, and community economic empowerment, their implementation still faces a number of challenges. This study used a qualitative research method with a descriptive-analytical approach. The results show that, although in general, Village Fund management in Muara Muntai Ulu Village has shown positive achievements in increasing access to basic services and economic empowerment, significant obstacles remain that hinder the policy's effectiveness. These obstacles include the limited capacity of village officials in planning and reporting, suboptimal community participation, inaccurate beneficiary data, and weak coordination between village institutions. In addition, the suboptimal utilization of Village Funds for productive economic innovation and a weak monitoring system are also challenges. Therefore, institutional capacity building, data system improvements, and mainstreaming of public participation are needed so that Village Funds truly contribute to community welfare comprehensively and sustainably.